2019
DOI: 10.3389/fped.2019.00099
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Intestinal Microbiota in Very Low Birth Weight Infants With Extrauterine Growth Restriction

Abstract: Objective: Very low birth weight (VLBW) infants, which experience significant postnatal growth restriction at the time of discharge, are at high risk of later growth failure and long-term consequences. This study aims to characterize the structure of intestinal microbiome community in VLBW infants with extrauterine growth restriction (EUGR). Methods: Twenty-three VLBW infants appropriate for gestational age (GA) hospitalized at the neonatal intensive care unit of the BaoAn Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Twin neonates born by C-section are colonized by dominance of four phyla including Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. This result was consistent with a previous study aiming to characterize the structure of intestinal microbiome community in very low birth weight infants with extrauterine growth restriction (Li et al, 2019) and infant twin pairs (Maqsood et al, 2019), in which the main phyla were the four phyla and Proteobacteria was the most abundant phylum among them. It was also reported in former studies that Proteobacteria and Firmicutes were the main phyla represented during the first days of life in the feces of C-sectiondelivered (Jakobsson et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Twin neonates born by C-section are colonized by dominance of four phyla including Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. This result was consistent with a previous study aiming to characterize the structure of intestinal microbiome community in very low birth weight infants with extrauterine growth restriction (Li et al, 2019) and infant twin pairs (Maqsood et al, 2019), in which the main phyla were the four phyla and Proteobacteria was the most abundant phylum among them. It was also reported in former studies that Proteobacteria and Firmicutes were the main phyla represented during the first days of life in the feces of C-sectiondelivered (Jakobsson et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Li et al (52) demonstrated that preterm infants with growth failure have a distinct intestinal microbiome's profile when compared to infants with normal growth at postnatal days 1 and 28. At both time points, the sole highly abundant taxa in the EUGR group was the genus Parabacteroides, which is a gram-negative, anaerobic, non-spore forming genus.…”
Section: The Preterm Gut Microbiota and Growing Impairmentmentioning
confidence: 99%
“…Intestinal microbiota plays an important role in human health and disease ( 1 ). In recent years, numerous studies have shown that infant intestinal microbiota affects the growth and development of children ( 2 , 3 ), and are associated with neonatal sepsis, neonatal necrotizing enterocolitis ( 4 ), childhood obesity ( 5 ), asthma, eczema ( 6 ), and diabetes ( 7 ), hypertension ( 8 ), and other diseases in adulthood. It is commonly believed that the uterus is sterile and the colonization of microbiota began after birth.…”
Section: Introductionmentioning
confidence: 99%